Juridical Analysis of Bankruptcy Statement Based on Commercial Court’s Verdict to Commanditaire Vennootschap - Henny Damaryanti; Aleksander Sebayang; Annurdi Annurdi (International Journal of Multi Discipline Science, 2018)
In conducting businessactivity, it is possible that a commanditaire vennootshcap (CV) has some debts to other parties, which is the debt is one of the requirements in the petition for bankruptcy statement. Based on this matter, it is interesting to examine the verdict of commercial court related to the declaration of bankruptcy decision experienced by CV as a non-legal entity. This research type is normative juridical research, and the data used for this research are some legislations, documents and books relating bankcruptcy law. The result of this research revealed that CV is a non-legal entity. Thus, it should not be a CV. Maju Jaya Bogor that is declared bankrupt in this case, but complementary ally (active) from CV Maju Jaya Bogor.